KULINER YOGYAKARTA, DARI IDENTITAS KE KOMODITAS - Hugo S. Prabangkara (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2018)
There is an interesting phenomenon within the context of culinary development in Yogyakarat, that is the arrival of “contemporary” culinary products endorsed by celebrities called Jogja Scrummy (JS) since 2014 and marketed through strong advertisement especially through social media (YouTube and Instagram) and websites. Such phenomenon can be found in other areas at almost the same time, and yet they are accompanied by narratives of identities, local languages, even local names which are disconnected with the marketed-products (which tend to be western- style cakes). I observe that there is a commodification of culinair which orginally tied with identity which turned to become commodity. This commodification is related with the State’s desire to increase local (even national) financial and budget which in turn promotes the productivity of the Indonesian middle class by separating which local culinary product is more porfitable which one isnot. This paper focuses on literatures on culinair as also website and video commercials/advertisments. I am focusing on narratives of local identities being employed in theseadvertisments. This focuses then are being read through “everyday nationalism” and the ideas of cosmopolitanism. The final question need to be answered is if these culinary commodification banal-ised local identities in culinary tradition or celebrated them?